Une première approche de la lexicographie provençale de l’occitan médiéval au XVIIIe siècle - David Fabié (Lengas)
We study in this paper the works of two Provençal lexicographers of medieval Occitan in the eighteenth century: Henri de Thomassin de Mazaugues (Aix, 1684-1743) and François Lacombe (Avignon, 1726 - Montpellier, 1794 or 1795). Mazaugues is the author of a Dictionnaire ou explication des mots provenceaux les plus anciens et les plus difficiles dont se servoient les troubadours known thanks to a copy (1790) by Alexandre Fauris de Saint-Vincens (1750-1819). Our analysis of this dictionary shows that it has been written in 1742-1743 from the reading of the Vida de sant Honorat (ca 1300) of Raimond Vidal. François Lacombe has composed two Dictionnaires du vieux langage françois (1766, 1767) regarded as the first printed attempts of medieval Romance languages lexicography in France. The study of these two books reveals that regarding medieval Occitan and French, they are actually made of borrowings, most often of poor quality, to previous works.